2018
DOI: 10.1287/msom.2017.0644
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Profitability and Quality of Service in Carshare Systems Under Demand Uncertainty

Abstract: Carsharing has been considered as an effective means to increase mobility and reduce personal vehicle usage and related carbon emissions. In this paper, we consider problems of allocating a carshare fleet to service zones under uncertain one-way and round-trip rental demand. We employ a two-stage stochastic integer programming model, in the first stage of which we allocate shared vehicle fleet and purchase parking lots or permits in reservation-based or free-floating systems. In the second stage, we generate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…A review of this literature can be found in Freund et al (2019) and He et al (2019b). Recent papers include Lu et al (2017) and Kabra et al (2018).…”
Section: On-demand Rental Networkmentioning
confidence: 99%
“…A review of this literature can be found in Freund et al (2019) and He et al (2019b). Recent papers include Lu et al (2017) and Kabra et al (2018).…”
Section: On-demand Rental Networkmentioning
confidence: 99%
“…Due to the complexity of the problem, they proposed a heuristic algorithm to obtain an approximate solution or to provide an initial heuristic solution. Lu et al [23] introduced a stochastic model to optimize the profitability and quality of service (QoS) considering uncertain one-way and twoway rental demand for a hybrid reservation-based and freefloating system. A desired QoS level was maintained by minimizing the expected penalty of unserved customers in a risk-neutral model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies like [4], [6], [7] merely took part of them into account and ingored the potential risk. Although Lu et al [23] briefly introduced a model that applied CVaR to reduce the risk of unserved demand, rare carsharing studies have considered the risk to avoid heavy losses. Thus, to fill in the research gaps, this paper considers a new riskaverse stochastic model to solve the joint design problem.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Weikl and Bogenberger (2015) translate this concept into a relocation model for free‐floating carsharing with electric vehicles that combines relocations with service trips to reduce overall costs. Lu, Chen, and Shen (2018) focus on the inherent uncertainty associated with carsharing operations and introduce a zone‐based model that can be applied to both station‐based and free‐floating systems.…”
Section: Background and Research Frameworkmentioning
confidence: 99%